Evaluation and Analysis of Mental Health Level of College Students With Financial Difficulties Under the Background of COVID-19 - Feng, Yongpeng; Zhang, Yunting (Frontiers in Psychology, 2021)
Against the backdrop of COVID-19, the mental health of college students with financial difficulties deserves scientific attention. This paper on the relationship between mental resilience and the mental health of students with financial difficulties summarizes the research on the psychological resilience of students with financial difficulties during the COVID-19 pandemic. It also suggests ways in which to improve the mental health levels of students with financial difficulties by improving their mental resilience.